2009
DOI: 10.1016/j.ejpain.2008.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Lack of efficacy of alpha‐lipoic acid in burning mouth syndrome: A double‐blind, randomized, placebo‐controlled study

Abstract: The fairly high placebo effect observed is very similar to data obtained from patients affected by atypical facial pain. This study failed to support a role for ALA in the treatment of BMS, and further investigations are needed to identify the cause of BMS in order to develop efficacious therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
175
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(180 citation statements)
references
References 21 publications
2
175
0
3
Order By: Relevance
“…The follow-up interview by phone call showed improvement of intraoral burning sensations in both groups (Omeprazole 40 mg twice a day in LPR patients, 600 mg of alpha-lipoic acid once a day in patients without LPR). Carbone et al [39] could show lack of efficacy of alphalipoic acid in burning BMS patients in a double blind, randomized, placebo-controlled study. Response rates of about 30% were found in the treatment groups as well as in the placebo group.…”
Section: Discussionmentioning
confidence: 98%
“…The follow-up interview by phone call showed improvement of intraoral burning sensations in both groups (Omeprazole 40 mg twice a day in LPR patients, 600 mg of alpha-lipoic acid once a day in patients without LPR). Carbone et al [39] could show lack of efficacy of alphalipoic acid in burning BMS patients in a double blind, randomized, placebo-controlled study. Response rates of about 30% were found in the treatment groups as well as in the placebo group.…”
Section: Discussionmentioning
confidence: 98%
“…The communication of different therapeutic measures to control the BMS is wide in the world literature (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The Gabapentin was used by White et al (15) in a case of a patient with BMS obtaining healing of the case and it was subsequently used by Heckmann et al (16) who conducted a study with gabapentin in 15 patients, where the initial dose was 300 mg / day and then grew at a rate of 300 mg every 48 hours to a maximum of 2400 mg / day.…”
Section: Discussionmentioning
confidence: 99%
“…It also exerts a neuro-regenerative action, because it crosses the hematoencephalic barrier and has a protective effect of brain and nerve tissue (10,11). A systematic review of the Cochrane Collaboration, noted that Alpha-Lipoic Acid (ALA) may help in management of burning mouth syndrome (12). Various studies have shown that the use of ALA did not produce greater benefits on the burning mouth that the use of placebos (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…According to the researchers, it is necessary to combine psychotherapy with the drugs, the reason for this being that psychogenic alterations are known to have a strong relation to BMS [2]. Carbone et al [67], López-Jornet et al [68] and Cavalcanti and Silveira [29] were not able to demonstrate any significant improvement in BMS patients when utilizing alpha-lipoic acid. Both the placebo effect and the different parameters that were used to calculate the intensity of the symptoms could be the source of possible explanations that account for such conflicting results.…”
Section: Treatmentmentioning
confidence: 99%